TGFβ1-Induced Differentiation of Human Bone Marrow-Derived MSCs Is Mediated by Changes to the Actin Cytoskeleton - Mona Elsafadi; Muthurangan Manikandan; Sami Almalki; Mohammad Mobarak; Muhammad Atteya; Zafar Iqbal; Jamil Amjad Hashmi; Sameerah Shaheen; Nehad Alajez; Musaad Alfayez; Moustapha Kassem; Raed Abu Dawud; et al. (Stem Cells International)
TGFβ is a potent regulator of several biological functions in many cell types, but its role in the differentiation of human bone marrow-derived skeletal stem cells (hMSCs) is currently poorly understood. In the present study, we demonstrate that a single dose of TGFβ1 prior to induction of osteogenic or adipogenic differentiation results in increased mineralized matrix or increased numbers of lipid-filled mature adipocytes, respectively. To identify the mechanisms underlying this TGFβ-mediated enhancement of lineage commitment, we compared the gene expression profiles of TGFβ1-treated hMSC cultures using DNA microarrays. In total, 1932 genes were upregulated, and 1298 genes were downregulated. Bioinformatics analysis revealed that TGFβl treatment was associated with an enrichment of genes in the skeletal and extracellular matrix categories and the regulation of the actin cytoskeleton. To investigate further, we examined the actin cytoskeleton following treatment with TGFβ1 and/or cytochalasin D. Interestingly, cytochalasin D treatment of hMSCs enhanced adipogenic differentiation but inhibited osteogenic differentiation. Global gene expression profiling revealed a significant enrichment of pathways related to osteogenesis and adipogenesis and of genes regulated by both TGFβ1 and cytochalasin D. Our study demonstrates that TGFβ1 enhances hMSC commitment to either the osteogenic or adipogenic lineages by reorganizing the actin cytoskeleton.